PENERAPAN RESTORATIVE JUSTICE TERHADAP PELAKU TINDAK PIDANA PENGANIAYAAN (Studi Kasus Kekerasan di Tangerang) - Riko Dony Rahardianto; Muhammad Rafli Marwah; Hendra Septiary; Widy Nurhasanah (Cross-border, 2022)
In society, some problems arise between individuals and groups. Criminal ACTS committed by perpetrators can have an impact, both physical and psychological on the victim. One form of the societal problem is criminal abuse, both light and severe, set up in chapters 351 of the criminal code and under 355 of the criminal code. The resolution of criminal abuse within the family circle, ideally looking for an alternative to undo the situation to prevent hereditary discord. Currently, in the case of misdemeanors, it can be handled through a restorative justice approach. This approach is judged as a new method of solving crimes and is intended to create justice and balance, as well as to avoid prison crime, especially in cases categorized as misdemeanors. The objective of this study is to find out how the implementation of restorative justice against perpetrators of abuse in case studies was attacked. The method used in this study USES a normative-jurisdictional approach. The result of this study shows that the implementation of restorative justice in the completion of a criminal act of light abuse is considered to be effective as a case settlement innovation and is carried out by applicable legal principles.